3D reconstructions of a controlled bus bombing. (March 2018) - Villa, Chiara; Hansen, Nikolaj Friis; Hansen, Kamilla Maria; Hougen, Hans Petter; Jacobsen, Christina
Abstract: Objectives: to demonstrate the usefulness of 3D reconstructions to better understand the dynamic of a controlled bus bombing. Materials and methods: 3D models of the victims (pigs) were created from post-mortem CT scanning using Mimic software; 3D models of the crime scene (bus) were generated by means of photogrammetry and modelling techniques, using Photomodeler and 3Ds max software applications. Combinations and visualizations of the scene before and after the explosion were created using 3Ds max. Results: several 3D reconstructions of the scene before and after the explosion were re-created to better visualize the dynamic of the incident and the blast injuries. All the pigs suffered extensive blast injuries. The bomb pig and the green pig (adjacent to the detonation site) underwent traumatic amputation and destruction due to a combination of blast injuries. Primary blast injuries and secondary injuries were found in all the other pigs. Fractures both due to tertiary or combined blast injuries were found in all the pigs except the yellow one (far from the detonation side). Three different "injury zones" could be identified based on the severity of the injuries of the pigs, as evaluated from autopsy and CT scanning. Conclusion: 3D reconstructions give a clearer and more comprehensive view of the scene and the victims, allowing a better understanding of the entire scene. CT scanning has proved to be an important tool in evaluating blast injuries in dead victims. Highlights: 3D reconstructions enable a comprehensive view of the scene and victims. PMCT scanning is an important tool to evaluate blast injuries. Primary blast injuries to the lungs can be clearly evaluated in PMCT. Primary blast injuries to the intestine are better evaluable during autopsy. Debris, foreign objects and fractures can be clearly identified in PMCT.